Highly efficient heterogeneous copper-catalyzed decarboxylative cross-coupling of potassium polyfluorobenzoates with aryl halides leading to polyfluorobiaryls. Issue 55 (11th July 2017) - Lin, Yang; Cai, Mingzhong; Fang, Zhiqiang; Zhao, Hong
Abstract : The decarboxylative cross-coupling of potassium polyfluorobenzoates with aryl halides has been achieved using a recyclable MCM-41-immobilized 1, 10-phenanthroline copper(i ) complex. Abstract : The heterogeneous decarboxylative cross-coupling reaction of potassium polyfluorobenzoates with aryl iodides and bromides was achieved in diglyme or DMAc at 130 or 160 °C in the presence of 10–20 mol% of a 1, 10-phenanthroline-functionalized MCM-41-immobilized copper(i ) complex, [MCM-41-Phen-CuI], yielding a variety of polyfluorobiaryls in good to excellent yields. This heterogeneous copper(i ) complex could easily be prepared via a simple procedure from commercially readily available and inexpensive reagents, exhibited the same catalytic activity as the homogeneous CuI/Phen system, and was recovered by filtration of the reaction solution and recycled at least 8 times without significant loss of catalytic activity.